(untitled) (Journal of Academic Research, 2023)
This paper was devoted to a real practical case study, where the performance of the medium voltage network (11/30 kV) in the Misurata Central Loop, was studied, analyzed, and evaluated for an of five years so as to predict the network’s performance and its ability to meet customer needs in the future. The aim of this research is to evaluate the performance of the medium voltage network in the Misurata Central Loop in terms of voltage drop, power losses, and loadability, estimate load growth for the next five years, resimulate the network, and make appropriate decisions to improve performance. The well-known NEPLAN program was used to evaluate performance indicators, based on data obtained from the General Electricity Company. The weaknesses found in the network were treated, and series conclusions are made. The results obtained from the program were tabulated and included, and these results were compared before and after treatment.